Simvastatin Suppresses Human Breast Cancer Cell Invasion by Decreasing the Expression of Pituitary Tumor-Transforming Gene 1 - Yin, Litian; He, Zhongmei; Yi, Bing; Xue, Linyuan; Sun, Jianxin (Frontiers in Pharmacology, 2020)
Statins, or 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors, have been widely used to lower cholesterol and prevent cardiovascular diseases. Recent preclinical and clinical studies have shown that statins exert beneficial effects in the management of breast cancer, while the underlying mechanisms remain to be elucidated. Herein, we sought to investigate the effect of statins on the expression of pituitary tumor-transforming gene 1 (PTTG1), a critical gene involved in human breast cancer invasion and metastasis. Our results showed that PTTG1 is highly expressed in malignant Hs578T and MDA-MB-231 breast cancer cell lines as compared with normal or less malignant breast cancer cells. Furthermore, we found that the expression of PTTG1 was markedly suppressed by lipophilic statins, such as simvastatin, fluvastatin, mevastatin, and lovastatin, but not by hydrophilic pravastatin. In a dose and time dependent manner, simvastatin suppressed PTTG1 expression by decreasing PTTG1 mRNA stability in MDA-MB-231 cells. Both siRNA-mediated knockdown of PTTG1 expression and simvastatin treatment markedly inhibited MDA-MB-231 cell invasion, MMP-2 and MMP-9 activity, and the expression of PTTG1 downstream target genes, while ectopic expression of PTTG1 promoted cancer cell invasion, and partly reversed simvastatin-mediated inhibition of cell invasion. Mechanistically, we found that inhibition of PTTG1 expression by simvastatin was reversed by geranylgeranylpyrophosphate (GGPP), but not by farnesylpyrophosphate (FPP), suggesting the involvement of geranylgeranyl synthesis in regulating PTTG1 expression. Our results identified statins as novel inhibitors of PTTG1 expression in breast cancer cells and provide mechanistic insights into how simvastatin prevent breast cancer metastasis as observed in recent preclinical and clinical studies.